The influence of resource complementary, technology competence and supply chain risk criteria on supply chain collaboration (case study of export import activities in Indonesia) - Hally Hanafiah; Anton Wachidin Widjaja (President University, 2022)
The instability and failure of implementing supply chain collaboration in all industries to date remain quite high. The selection of partners is one of the many factors determining the success of the collaboration, which is very limited in the research conducted. So that the influence of partner selection criteria on the success of this collaboration is the background of this research. The notion of work-related motivation and consideration of partners is still a parameter that is often used in previous research. Technological advances and the current business environment conditions that cause supply chain collaboration to be required to process information sharing and share possible risks that occur, the criteria for partner technology competence and partner supply chain risks become additional criteria that determine the success of the collaboration. In addition to examining the dominant partner criteria to improve company performance, this study will also examine the contribution of supply chain collaboration to company performance through collaborative benefits. Descriptive analysis, measurement model, and structural model using Structural Equation Model (SEM) with a scale of 6 Likert used in quantitative research on 151 companies providing export and import services in Indonesia.